Congenital Oesophageal Stenosis Diagnosed at 15 Days of Age: A Rare Case Report - Shahidullah, Shabnam; Sultana, Naima; Sarkar, Aditi; Nesa, Vikarun; Roy, Sunirmal; Begum, Nurun Nahar (Sir Salimullah Medical College Journal, 2022)
Congenital oesophageal stenosis is a rare entity with a frequently delayed diagnosis. Patients are often treated according to diagnosis of GERD until intolerance to semisolid diet appears and CES is suspected. It usually presents in infancy and childhood. We are reporting a case of congenital 0esophageal stenosis in fifteen days old male child. It is very rare to diagnose congenital oesophageal stenosis at this age. Sir Salimullah Med Coll J 2022; 30: 96-99